Introduction - Jasnos, Renata (Studia Paedagogica Ignatiana, 2018)
The Department of the Cultural and Christian Foundations of Education in the Institute of Educational Sciences of the Jesuit University Ignatianum in Krakow undertook a multi-stage research project in 2013 entitled “The educational inﬂuence of the Church in the context of socio-cultural changes”. The ﬁrst stage of the research project’s goals was concerned with the educational milieu and the results of it wear published in the scientiﬁc series “Cultura – Spiritualitas – Educatio.” The present publication, devoted to the authority of the Church and her educational mission in the context of socio-cultural changes, is the effect of the second stage of the project. The question of authority is the subject of numerous studies car- ried out mainly in the social sciences. In relation to education as a broadly understood concept, particular interest is raised in con- nection to the relationship between the parties of the educational process, the dynamics of this relationship in the maturation process of young people and the phenomenon of interactions related to the educator’s authority as deﬁned by this relationship. The authority in the process of upbringing is a subject that has been undertaken for a long time but still needs to be updated and revised.